Utilization of Instagram as a Marketing Communication Media - A zzahra Tri Najla; M. Fahrizal Adrian; Mutyara KD Chairunissa Pohan; Nasyuwah Sabila Hasibuan; Suhairi Suhairi (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
One of the shops that uses Instagram as a marketing medium is the online shop Grosirolshop.id which sells goods such as clothing, accessories, headscarves, shoes, bags, makeup tools. One of the features used to introduce their product is only through a short photo/video that is uploaded, which gets a positive response from potential customers. From this presentation, this study aims to find out how digital marketing marketing communication is through Instagram media used by the owner of the Grosirolshop.id online shop. The research method in conducting this research is a qualitative method. The results show that marketing communications are carried out through Instagram media used by the owner of the Grosirolshop.id online shop through promotion on the Instagram application. Of the various Instagram built-in support features, the features most frequently used are the Instastory photo upload feature and Story Highlights. In the instastory feature, Grosirolshop.id uses it to inform the latest products and store situations every day. Meanwhile, for uploading photos, Grosirolshop.id uses it to post new products with an attractive layout. Highlights Story is used to provide important information such as how to order online, store location instructions, shopee address and more. The features used are felt to be very effective and helpful in the promotion process of Grosirolshop.id products, because they can convey direct messages to consumers .